2004
DOI: 10.1103/physrevlett.93.223001
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Rescattering in Intense, Femtosecond Laser Interactions with a Negative Ion

Abstract: It is now well established that energetic electron emission, nonsequential ionization, and high harmonic generation, produced during the interaction of intense, femtosecond laser pulses with atoms (and atomic positive ions), can be explained by invoking rescattering of the active electron in the laser field, the so-called rescattering mechanism. In contrast for negative ions, the role of rescattering has not been established experimentally. By irradiating F ÿ ions with ultrashort laser pulses, F ion yields as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
27
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 23 publications
1
27
0
Order By: Relevance
“…36,37 On the basis of increased rates for linear versus circular laser polarizations, Pedregosa-Gutierrez et al reported evidence for a non sequential rescattering mechanism in intense field double detachment of atomic F − . 29 Nevertheless, we recently reported efficient multiple detachment of molecular SF 6 − anions exhibiting weak dependence on laser polarization that excludes the possibility of a semiclassical rescattering type mechanism. 38 As the parent SF 6 + cation is not found, SF n + fragments, as well as high-lying dissociation channels leading to atomic S + and F + products are observed.…”
Section: ■ Introductionmentioning
confidence: 99%
“…36,37 On the basis of increased rates for linear versus circular laser polarizations, Pedregosa-Gutierrez et al reported evidence for a non sequential rescattering mechanism in intense field double detachment of atomic F − . 29 Nevertheless, we recently reported efficient multiple detachment of molecular SF 6 − anions exhibiting weak dependence on laser polarization that excludes the possibility of a semiclassical rescattering type mechanism. 38 As the parent SF 6 + cation is not found, SF n + fragments, as well as high-lying dissociation channels leading to atomic S + and F + products are observed.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In addition, the absence of the Coulomb potential makes it easier for the electron wavepacket to spread out, reducing the effect of rescattering [4,5]. While evidence for rescattering from negative ions has been found experimentally [11], no verification has yet been provided from ab initio theory. A theoretical approach, based on first order correction to the strong field approximation, was able to reproduce experimental results from Br − and F − , [12] but a more recent study, using a numerical solution of the time-dependent Schrödinger equation (TDSE), found "no qualitative evidence of rescattering" for H − [13].…”
mentioning
confidence: 95%
“…Since for E γ ≈ |E 0 | the tunnelling picture is not appropriate, we generally denote this nonperturbative regime of intense laser-atom interactions as the multiphoton regime. This latter regime is relevant to recent experiments on the interaction of standard femtosecond sources (i.e., λ = 800 nm) with negative ions [9] (in which case E γ ≈ 0.5|E 0 |, where |E 0 | is the electron affi nity) and of intense infrared pulses (i.e., λ = 3.5 μm) with alkali atoms in excited states [10]; it also applies to forthcoming experiments for rare gases interacting with the intense vuv and soft x-ray radiation produced by free-electron lasers. Based upon an exactly solvable quantum model, we predict that plateau-like structures should appear in the spectra for all bound-bound (as in HG), bound-free (as in ATI/ATD) and free-free (as in LAES) multiphoton transitions in a high-frequency fi eld having E γ ≤ |E 0 | provided that the ponderomotive energy exceeds the photon energy, i.e.…”
mentioning
confidence: 94%